Practical data communications for instrumentation and control - Park, John, 1953- (Practical professional books from Elsevier.)
Instrumentation and control systems are highly reliant on data communications, so a working knowledge of the latest communications technologies and the essential protocols is essential for anyone designing, specifying or using instrumentation and control systems. This book is the only title on the market designed specifically for this audience. This is a comprehensive treatment of industrial data communication systems. Commencing with a thorough discussion of the popular RS-232, RS-422 and RS-485 standards it then moves on to industrial protocols, industrial networks and the communication requ.